Development of nanostructured electrode material and its characterization for solid oxide fuel cells. (2018) - Kavitha, K.; Althaf, R.; Venkat, V.C.; Kumar, N. Suresh; Rani, S. Subha; Ashok, Anuradha M.
Abstract: Nano structured ceramic powders composition of La0.6 Sr0.4 Co0.2 Fe0.8 O3 (LSCF) and La0.4 Sr0.4 TiO3 (LST) were prepared by sol-gel process using nitrate based chemicals. In an effort to obtain improved conductivity behaviour, these perovskites were synthesised as nanostructured materials. After thermal and structural analysis, their electrical properties were studied through impedance spectroscopy. XRD patterns reveal single-phase formation with average particle size of 11.48 nm and 23.7 nm for calcined powders of LSCF and LST. SEM analysis of the sintered electrodes revealed uniform grain boundary distribution with porous structure. Electrochemical AC impedance analysis showed the total conductivity of LSCF and LST oxides to be 8.60×10 -5 S/cm and 7.61×10 -6 S/cm at 800 C.